Correction: Theoretical prediction of the electronic structure, optical properties and photocatalytic performance of type-I SiS/GeC and type-II SiS/ZnO heterostructures (vol 13, pg 7436, 2023) - Sabir, S. S.; Din, Haleem Ud; Ahmad, Sheraz; Alam, Q.; Sardar, S.; Amin, B.; Farooq, M.; Nguyen, Cuong Q.; Nguyen, Chuong V. (Royal Society of Chemistry, 2023)
Correction for 'Theoretical prediction of the electronic structure, optical properties and photocatalytic performance of type-I SiS/GeC and type-II SiS/ZnO heterostructures' by S. S. Sabir et al., RSC Adv., 2023, 13, 7436-7442, https://doi.org/10.1039/d3ra01061a.